Recent Advances in 2D Layered Phosphorous Compounds. Issue 4 (25th January 2021) - Zhang, Yue; Fan, Taojian; Yang, Sijie; Wang, Fakun; Yang, Sanjun; Wang, Shuzhe; Su, Jianwei; Zhao, Mei; Hu, Xiaozong; Zhang, Han; Zhai, Tianyou
Abstract: 2D layered phosphorous compounds (2D LPCs) have led to explosion of research interest in recent years. With the diversity of valence states of phosphorus, 2D LPCs exist in various material types and possess many novel physical and chemical properties. These properties, including widely adjustable range of bandgap, diverse electronic properties covering metal, semimetal, semiconductor and insulator, together with inherent magnetism and ferroelectricity at atomic level, render 2D LPCs greatly promising in the applications of electronics, spintronics, broad‐spectrum optoelectronics, high‐performance catalysts, and energy storage, etc. In this review, the recently research progress of 2D LPCs are presented in detail. First, the 2D LPCs are classified according to their elemental composition and the corresponding crystal structures are introduced, followed by their preparation methods. Then, the novel properties are summarized and the potential applications are discussed in detail. Finally, the conclusion and perspective of the promising 2D LPCs are discussed on the foundation of the latest research progress. Abstract : 2D layered phosphorous compounds are promising in energy storage, catalysis, optoelectronics, semiconductor devices and others for their rich elemental composition, structure diversity, and novel physical properties. In this review, the research progresses of 2D layered phosphorous compounds in recent years are systematically summarized.